Synthesis and Crystal Structure of 2,2’-(1,2-Ethylenedioxy)bisbenzaldehyde O,O’-Diethyldioxime - Zhao, Li; Zhang, Yu-Jie; Zhang, Shou-Ting; Guo, Hong-Xia; Cheng, Qian (Asian Journal of Chemistry, 2013)
The compound, 2,2'-(1,2-ethylenedioxy)-bis-benzaldehyde O,O'-diethyldioxime, has been synthesized by 2,2'-(1,2-ethylenedioxy)-bis-benzaldehyde O,O'-diethyldioxime and ethoxyamine hydrochloride in ethanolic solution and characterized structurally by X-ray crystallography. The molecule of the title compound adopts an extended conformation where the two oxime groups are apart from each other. The two benzene rings are parallel to each other. In the crystal structure, intermolecular C7-H7···O2 hydrogen bonds link the molecules forming an infinite 1D chain-like supramolecular structure.